Self-Regulation of Learning in Ballet Instruction for Contemporary Dancers: Psychopedagogical Implications of Mental Imagery and Embodied Cognition - Alfaro Herrera, Mariana (2025)
This article analyzes the implications of mental imagery and the principles of embodied cognition in ballet instruction for contemporary dancers, exploring their relationship with self-regulated learning. The theoretical foundations of self-regulation, mental imagery, and embodied cognition theory as an integrative framework are reviewed, analyzing their influence on the development of creative and interpretative skills aimed at a pedagogical proposal for ballet learning. The conclusion is that the use of these principles can facilitate exploration, the creation of movements and metaphors, as well as the establishment of a deeper synchronization between mind and body in the artistic performance of practitioners of this discipline.